On the Choice of Fiscal Adjustment to Financial Crises: Expansionary vs. Contractionary Policies - Čekanavičius, Linas (Ekonomika, 2018)
[full article and abstract in English]An everlasting debate over the economic policies to be implemented in the face of economic recessions tends to intensify every time such a crisis strikes. Two notably opposite schools have emerged: one that represent those who advocate for quantitative easing and increased government spending, and another that calls for austerity measures and disciplined public finance. The available empirical evidence cannot supply a definite solution to the spending vs. austerity debate if just one answer is to be provided, as there are numerous historical experiences when either strategy had worked or failed. The aim of this paper is to examine and assess the arguments of both schools of economic policies, to highlight the essential drawbacks and limitations of both and to identify the specific conditions under which each of the policy type can bring the desired impact. It is argued that both of the policy approaches rely on particular implicit assumptions and, if implemented recklessly, are liable to fail or create negative side-effects. A discussion of the relative merits and shortcomings of both types of recipes for curing economic recessions is illustrated by the references to the empirical historical cases. The main conclusion that stems out of the analysis is that a somewhat “medical approach” should be followed while attempting “to cure” ailing economies: regardless that the symptoms of a slump might be quite similar, one should start with an attempt to diagnose the underlying causes of the economic malady at hand, followed by the assessment of a “patient’s” health status, and only then proceed to the selection of an appropriate “cure” and treatment procedure.
Keywords: recession, government spending, austerity, comparative analysis